Trends, risk factors and prognostic implications of postoperative stroke after heart transplantation: an analysis of the UNOS database. (14th October 2021) - Briasoulis, A; Doulamis, I; Kampaktsis, P; Alvarez, P
Abstract: Background: Post-operative stroke increases morbidity and mortality after cardiac surgery. Data on characteristics and outcomes of stroke after heart transplantation (HT) are limited. Methods: We conducted a retrospective analysis of the UNOS database from 2009 to 2020 to identify adults who developed stroke after orthotropic HT. HT recipients were divided according to the presence or absence of postoperative stroke. The primary endpoint was all-cause mortality after HT. Results: A total of 25, 015 HT recipients were analyzed, including 719 (2.9%) patients who suffered perioperative stroke. The rates of stroke increased from 2.1% in 2009 to 3.7% in 2019 and the risk of stroke was higher after the implantation of the new allocation system (odds ratio 1.29, 1.29, 95% Confidence Intervals [CI] 1.06–1.56, p=0.01). HT recipients with postoperative stroke were older (p=0.008), with higher rates of prior cerebrovascular accident (CVA) (p=0.004), prior cardiac surgery (p<0.001), longer waitlist time (p=0.04), higher rates of extracorporeal membrane oxygenation support (ECMO) (p<0.001), left ventricular assist devices (LVAD) (p<0.001), mechanical ventilation (p=0.003) and longer ischemic time (p<0.001). After multivariable adjustment for recipient and donor characteristics, age, prior cardiac surgery, CVA, support with LVAD, ECMO, ischemic time and mechanical ventilation at the time of HT were independent predictors of postoperative stroke. Stroke was associated with increased risk of 30-day and all-cause mortality after HT (hazard ratio [HR] 1.49, CI 1.12–1.99, p=0.007). Conclusion: Perioperative stroke after HT is infrequent but associated with higher mortality. Redo sternotomy, LVAD and ECMO support at HT are among the risk factors identified. Funding Acknowledgement: Type of funding sources: None.